Environmentally Friendly, Photochemical Access to [N∧C∧N ]AuIII Pincer Complexes By Oxidative Addition. Issue 34 (1st June 2021) - Eppel, Daniel; Penert, Philipp; Stemmer, Johanna; Bauer, Christina; Rudolph, Matthias; Brückner, Margit; Rominger, Frank; Hashmi, A. Stephen K.
Abstract: Starting from commercially available DMSAuCl and diazonium salts, cationic [ N ∧ C ∧ N ]Au III complexes were synthesized in a selective, photosensitizer‐free, photochemical reaction by irradiation with blue LED light. This new protocol represents the first easy synthesis of these types of pincer complexes in moderate to excellent yield starting from a readily available gold(I) precursor with nitrogen as the only by‐product. Owing to the disadvantages of known protocols, especially the toxicity in the case of a transmetalation with mercury or the necessity for a mostly twofold excess of a gold precursor, this method offers an attractive alternative towards this kind of gold(III) complexes. In addition, the first arylated [ N ∧ C ∧ N ]Au(III) pincer complex was synthesized by using this technology. Abstract : The first selective general procedure for the rarely investigated [NCN]Au III complex class was developed. In a photochemical step, different gold(III) complexes can be easily synthesized, offering a fast entry to highly valued scaffolds for OLEDs, gas‐sensors or anticancer drugs, respectively. Both (DMS)gold chloride complexes or (DMS)gold organometallic compounds can be used as starting materials introducing the gold center (DMS=dimethylsulfide), which further expands the synthetic possibilities.